Young People and Intimate Partner Violence: Experiences of Institutional Support and Services in England - Barnes, Maria (Journal of family violence, 2024)
PurposeYoung people (YP) are at greater risk of experiencing intimate partner violence and abuse (IPVA), with high prevalence rates at 18–25 years and potentially severe short and long-term health and social impacts. YP often view adult support services as not for them and more research is needed to understand effective responses to IPVA among different groups.MethodsSemi-structured interviews alongside Life History Calendars were undertaken to explore 18 young peoples’ (18–25 years) experiences of community and service level responses to their IPVA between 2019–2020. Thematic analysis and case studies were carried out.ResultsParticipant accounts commonly described what did or did not help within: education; primary care physicians and maternity services; third sector or non-government support organisations; and counselling and support workers. YP wanted clearer information on identifying abuse from a younger age in schools and better access and signposting to specialist services. They benefited the most from equal power dynamics in relationships with professionals where they were supported to make their own decisions.ConclusionsProfessionals in all sectors (including schools) need IPVA trauma-informed training that encourages equal power dynamics, with a clear understanding of and access to referral pathways, to be able to respond to the needs of YP experiencing IPVA.